Electron-Beam Welding - Structural-Phase State and Microhardnes in the Weld Zone in a Submicrocrystalline Titanium Alloy Grade2; Materials Science Forum; Vol. 906 : Materials and Processing Technology - Klimenov V. A. Vasily Aleksandrovich; Klopotov A. A. Anatolii; Abzaev Yu. A.; Kurgan K. A.; Vlasov Yu. A. (2017, 2017)
Title screen